A genetic variant in PIK3R1 is associated with pancreatic cancer survival in the Chinese population. (6th May 2019) - Zhu, Ying; Ke, Juntao; Gong, Yajie; Yang, Yang; Peng, Xiating; Tian, Jianbo; Zou, Danyi; Yang, Nan; Wang, Xiaoyang; Mei, Shufang; Rao, Meilin; Ying, Pingting; et al.
Abstract: Pancreatic cancer is one of the deadliest malignancies with few early detection tests or effective therapies. PI3K‐AKT signaling is recognized to modulate cancer progression. We previously identified that a genetic variant in PKN1 increased pancreatic cancer risk through the PKN1/FAK/PI3K/AKT pathway. In order to investigate the associations between genetic variations in that pathway and pancreatic cancer prognosis, we conducted a two‐stage survival analysis in a total of 547 Chinese pancreatic cancer patients. Consequently, a variant, rs13167294 A>C in PIK3R1, was significantly associated with poor survival in both stages and with hazard ratio being 1.32 (95% CI = 1.13‐1.56, P = 0.0007) in the combined analysis. Function annotation and prediction suggested that genetic variants in this locus might affect overall survival of pancreatic cancer patients by regulating PIK3R1 expression. Abstract : We identified a variant in PIK3R1 associated with pancreatic cancer outcome, through a two‐stage survival analysis in the Chinese population.